Ask Question
24 January, 02:07

Let f (x) = x*2+2x-1 and g (x) = 2x-4 find 2f (x) - 3g (x)

+3
Answers (1)
  1. 24 January, 04:03
    0
    F (x) = x²+2x-1 and g (x) = 2x-4 2f (x) - 3g (x) = ?

    2f (x) = 2 * (x²+2x-1) = 2x²+4x-2

    3g (x) = 3 (2x-4) = 6x-12

    2f (x) - 3g (x) = (2x²+4x-2) - (6x-12) = 2x²+4x-2 - 6x+12 = 2x²-2x + 10

    2f (x) - 3g (x) = 2x²-2x + 10
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Let f (x) = x*2+2x-1 and g (x) = 2x-4 find 2f (x) - 3g (x) ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers